2013
DOI: 10.1159/000356639
|View full text |Cite
|
Sign up to set email alerts
|

A FRET-Based Approach for Quantitative Evaluation of Forskolin-Induced Pendrin Trafficking at the Plasma Membrane in Bronchial NCI H292 Cells

Abstract: Background: Human pendrin (SLC26A4, PDS) is an integral membrane protein acting as an electroneutral anion exchanger. Loss of function mutations in pendrin protein cause Pendred syndrome, a disorder characterized by sensorineural deafness and a partial iodide organification defect that may lead to thyroid goiter. Additionally, pendrin up-regulation could play a role in the pathogenesis of several diseases including bronchial asthma and chronic obstructive pulmonary disease (COPD). Therefore, monitoring the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that tolvaptan impairs the increase in cAMP levels upon vasopressin action . Here, the effect of tolvaptan on cAMP level was evaluated with FRET‐based EPAC biosensors as already described . Specifically, the FRET probe contains cAMP‐binding sequence of Epac1 sandwiched between ECFP (donor) and EYFP (acceptor).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that tolvaptan impairs the increase in cAMP levels upon vasopressin action . Here, the effect of tolvaptan on cAMP level was evaluated with FRET‐based EPAC biosensors as already described . Specifically, the FRET probe contains cAMP‐binding sequence of Epac1 sandwiched between ECFP (donor) and EYFP (acceptor).…”
Section: Resultsmentioning
confidence: 99%
“…CFP and YFP were excited at 436 and 500 nm, respectively; fluorescence emitted was measured at 480/40 nm for CFP and 535/30 nm for YFP and FRET. Corrected normalized FRET values were determined as already described (Rodighiero et al, 2008 ; Tamma et al, 2013 , 2017 ; Russo et al, 2017 ). Each image was corrected for CFP cross-talk and YFP cross-excitation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in vitro studies showed that mutation of a STAT6 binding motif abolished the IL4/IL13 effects on pendrin promoter activity [24]. Studies from our group showed that stimulation with forskolin or treatment with IL13 increased the abundance of pendrin in the plasma membrane of bronchial NCI-H292 cells [42,43], which may contribute to modulating the intracellular pH [42].…”
Section: Pendrin Expression and Function In The Airwaysmentioning
confidence: 94%